An approach to sustainable development from tourists' perspective. Empirical evidence in Romania - Dan-Cristian Dabija; Raluca Babut (Amfiteatru Economic Journal, 2013)
Developing businesses in compliance with the principles of sustainability has been a tough challenge in our century. A planned, integrated and properly coordinated orientation towards environment protection, involvement in activities of society and local communities, supporting and streamlining its own economic activities are the core elements whereby a business can obtain long-term harmonious development, a synergic evolution and a competitive advantage. The major problem, however, lies in the poor understanding of sustainable development directions and their difficult transposition into a business' current activity, in its proper funding and in finding consumers willing to pay the price of sustainable products and services. Whereas the literature deals with the application of dimensions of sustainable development in terms of holiday or business destinations, local communities and/or regional or national authorities, the management of tourist businesses etc, the study of tourist consumers' perception has been quite infrequent. As a matter of fact, few studies set to highlight how the dimensions of sustainable development implemented by tourist units are properly perceived by consumers and how these contribute to building and increasing consumers' satisfaction. Tourism, tourist business or tourist destination may be referred to as sustainable when they are so maintained and developed that they remain viable even infinitely without affecting environment, social, economic or cultural dimensions of the analyzed area (Butler, 1999). To overcome these shortcomings, the authors appealed to experimental research in an attempt to highlight tourists' perception of the three dimensions of sustainable development as they are implemented by tourist accommodation units in one of the biggest cities of Romania. Using a structural approach and appealing to econometrical modeling of 850 valid answers, the authors show how sustainable development actions conducted by tourist accommodation units may turn into genuine stimuli for building satisfaction. The conclusions reveal important managerial and scientific implications.
Keywords: L83; M30; M31; Q56; 330; Tourist business; sustainable development; hotels; sustainable tourism; environment protection; consumer satisfaction